Health and safety: psychosocial aspects of mental health & quality of life among survivors of flood disaster in Kelantan (PAMASK) - Hasanah, Che Ismail (Pusat Pengajian Sains Perubatan Universiti Sains Malaysia, 2017)
Flooding is the commonest type of natural disaster worldwide and its effect on people's mental health and economy is extensive. Such calamity was found to lead to deterioration of health status and to precipitate post-traumatic stress disorder (PTSD) and psychiatric disorders. In a systematic review of 35 relevant epidemiological studies. the prevalence of psychological distress among flood survivors wos 8.6% to 53% two years post-flood and can also exacerbate their physical illness [1]. The flood in Kelantan in December 2014 wos unprecedented in its scale of destruction. hitting mainly people in the lower socio-economic group that sustained living in agriculture. The National Security Council [NSC) confirmed the massive flood that hit Kelantan wos the worst in the history of the state [2]. Kelontan ~ in the northern, eastern coastal region of Malaysia, with four districts located along the main river, i.e. the Kelantan river. Galas and Lebir rivers are the main feeders to Kelantan river, ond Kola Bharu. Pasir Mas. Tumpat and Kuala Krai are the four major towns located along the river. The heavy monsoon rain from November to March brought an annual flood to Kelantan. However. a flood of the proportion of a national disaster was rather rare, and the 1wo before 2014 were in 1927 and 1967 [3]. The 2014 flood was considered to be a "lsunamHike disaster" in which 202.000 victims in Kelantan were d~placed [4]. The district of Kuala Krai was likened to a place attacked by a giant bird or the ancient 'garuda' [5]. Previous studies showed that the psychological health was significantly worse in the affected areas compared to non-attected areas [6. 7]. Unfortunately, there is a scarcity of published studies regarding the impact of flood disaster on mental health in Malaysia. A study on the psychological effects on vicfims of the Jahor flood 2006/2007 draws a conclusion based on an exploratory qualitative approach. where a total of live respondents were interviewed using face-to-face technique (8]. A survey on the psychological impact post-tsunami in Aceh and post-earthquake in West Sumatra Indonesia showed that 32%-57% of respondents being stressed. depressed or anxious [9]. However, the lime of survey and duration after the disaster was not declared, and the associations drawn from the study were based on just the chi-square test. Thus. the aftermath of the 2014 flood in Kuala Krai offered a situation with a somewhat homogenous population. Kuala Krai was one of the worst-hit districts with 90% of the district being affected by the flood. Information from the District Office revealed that the total number of houses damaged were 2030, and 14,700 families involved. The total number of flood victims in the d~trict was 70,035. The population was almost all Malays and Islam in religion, and they were mostly from lower socio-economic group. There is always a limitation in a cross-sectional study on the psychological impact of a disaster. This is because, there is almost always no data taken prior to the disaster. Ho'Never. in the past there were studies that compared areas that were affected and not affected by the flood. showing a higher prevalence of PTSD or PTSD-relaled symptomatology in the flooded area [6- 7]. It is expected that the threat and destruction brought by the flood is an extraordinary experience that is sufficient to precipitate a post-traumatic stress disorder. The objective of this study is to find out the rate and extent of the psychological disturbances in the population that was attected by the flood disaster. We also tested the research hypothesis that most of the mental disturbances in an area affected by a flood disaster ore attributable to PTSD. However. there are other factors that are likely to contribute to the psychological disturbances. The factors are: age, sex. income. occupation. medical illnesses, and the effect of flood such as property and financial loss. social and moral support. level or amount and satisfaction of flood aid received, on-going difficulties, etc.